Improvement of toughness and wear resistance in PBT composites via synergistic reinforcement of functionalized phenolic microspheres and tungsten carbide - Jaeyeon Kim; Jaekyung Lee; Oju Kwon; Subin Lee; Pei-Chen Su; Minhaeng Cho; Jooheon Kim (Journal of Materials Research and Technology)
The demand for high-performance polymer composites has driven research to enhance the mechanical, thermal, and tribological properties of polybutylene terephthalate (PBT). However, neat PBT suffers from limitations such as low thermal conductivity and poor wear resistance. To address these issues, we developed PBT composites reinforced with functionalized phenolic microspheres (FPM-BDO) and 3-mercaptopropyl trimethoxysilane-modified tungsten carbide (M − WC). The resulting FPM-BDO/M-WC/PBT composites exhibited significant improvements. The percolated heat conduction networks formed by M − WC increased thermal conductivity to 0.627 W/m·K, a 129 % enhancement over neat PBT. The addition of FPM-BDO improved crystallization, increasing crystallinity and tensile strength by 20.3 % while maintaining 94.3 % of the original elongation at break, overcoming the brittleness of neat PBT. Tribological performance was also enhanced, with a 46.1 % reduction in the coefficient of friction and a 50.6 % decrease in the specific wear rate. These improvements were attributed to effective load transfer, heterogeneous nucleation, and a free-volume expansion effect, which collectively enhanced strength, ductility, and wear resistance. The combined effect of FPM-BDO and M − WC successfully addressed the major limitations of neat PBT, making these composites promising for automotive, aerospace, and industrial applications that require high-performance, thermally stable, and wear-resistant materials.